Cochrane Database of Systematic Reviews 2015
DOI: 10.1002/14651858.cd007130.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Home-based versus centre-based cardiac rehabilitation

Abstract: Background-The burden of cardiovascular disease world-wide is one of great concern to patients and health care agencies alike. Traditionally centre-based cardiac rehabilitation (CR) programmes are offered to individuals after cardiac events to aid recovery and prevent further cardiac illness. Home-based cardiac rehabilitation programmes have been introduced in an attempt to widen access and participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 71 publications
1
78
0
11
Order By: Relevance
“…They are also shown to be efficacious [104][105][106][107] . The offering of alternative models was first reported in a 1997 publication from England and Wales 25 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…They are also shown to be efficacious [104][105][106][107] . The offering of alternative models was first reported in a 1997 publication from England and Wales 25 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A disponibilidade de programas realizados em casa ou em locais próximos do ambiente domiciliar oferece uma oportunidade de ampliar o acesso e participação na RCPM. [11][12][13] Tendo em vista o exposto, este estudo tem por objetivo verificar e comparar a aderência a um programa de reabilitação baseado a domicilio e identificar as barreiras que interferem na adesão. Após análise dos diários de treinamento físico foi possível observar que, um participante do GC precisou ser excluído da amostra final uma vez que este apresentou problemas de saúde durante a intervenção proposta (Crise de Otite).…”
Section: Introductionunclassified
“…Many studies have shown that a cardiac rehabilitation program consisting of aerobic and resistance training is an effective intervention to restore physical function 10,11) and exercise capacity, 12,13) and to reduce difficulty in physical activities of daily living 14,15) in cardiac patients. Several meta-analyses of randomized trials 12,16) have also confirmed that a cardiac rehabilitation program consisting of lifestyle modification and prolonged exercise training in the recovery phase (after hospital discharge) is more effective in reducing morbidity and mortality in cardiac patients. However, to our knowledge, this is the first study that adopted an exercise regimen to improve walking speed for a cardiac rehabilitation program during hospitalization, and that assessed the effects of inpatient cardiac rehabilitation on both walking speed at hospital discharge (short-term outcome) and cardiac events after hospital discharge (long-term outcome) in elderly patients with IHD.…”
Section: Discussionmentioning
confidence: 99%